The effect of alkaline treatment on water absorption and tensile properties of non-woven kenaf polyester composite - Zakaria, Mohd Nazarudin; Othman, Maizatulnisa (Trans Tech Publications, Switzerland, 2013)
The aim of this study is to determine the effect of alkali treatment on water absorption and tensile properties of non-woven kenaf polyester composite. Kenaf fiber mat was treated with 2, 4 and 6% of different sodium hydroxide (NaOH) concentration. The composite was fabricated using compression molding technique. It was found that treatment reduced the overall water uptake of composites. The 6% treated fibre composite was greater in moisture resistance as compared to untreated. The tensile strength of the composites was substantially improved after alkali treatment, and it was similar with the tensile modulus.